Collateral Damage. Online Reception of Tolstoy and Dostoevsky after the Invasion of Ukraine - Iris Uccello; Gabriele Vezzani (Umanistica Digitale)
The Russian invasion of Ukraine on February 24, 2022, triggered widespread cultural and geopolitical shifts, prompting a reevaluation of Russia’s historical and imperialistic narratives. This study examines how perceptions of Russian literature, specifically works by Tolstoy and Dostoevsky, have evolved among non-academic readers in the wake of these events. Using data from the Goodreads platform, we analyzed over 5,700 user reviews and ratings to determine whether the war influenced public reception. The results highlight a statistically significant, albeit small, decrease in ratings following the invasion, suggesting a growing cultural skepticism toward Russian literature. Computational techniques, such as Change Point Detection algorithms, identified January and February 2022 as pivotal moments in this trend. The findings also raise questions about the impact of cultural boycotts, fake reviews, and bots on shaping public sentiment. These insights call for further exploration into the interplay between political events and literary reception, especially in highly polarized contexts.